KONDISI DAN POTENSI DAMPAK PEMANFAATANAIR TANAH DI KABUPATEN SAMPANG DAN PAMEKASAN - Hendra Wahyudi (Universitas Negeri Yogyakarta, 2007)
The Madura Bridge is expected to be finished on the year of 2009 so that tl. Madura Island will be in the positive economic growth. To support those ofdevelopme in Madura Island, there must be supporting infrastructures need to be prepaired i. e. watl supply infrastructure.The water source in Madura Island is very low especially the surface watlsource. Meanwhile there hasn't been any research conducted on groundwater sconditic andpotension. So that it need to conduct a research on the utility effect ofgroundwater condition andpotention in Kabupaten Sampang and Kabupaten Pamekasan. The result shows that the total sum ofgroundwater sutility until now in Kabupatl Sampang is 101188.81 cu. m/day, meanwhile the total sum of groundwater s utility Kabupaten Sampang is 176761,93 cu.m/day, and the total sum of goundwater s utih in Cekungan Sampang-Pamekasan is about 214800 cu.m/day or 7840200 cu.m/yel The recharge amout is about 590090 cu.m/day or 215678000 cu.m/year. Meanwhile t, potention of groundwater s utility in Cekungan Ketapang is about 37100 cu.m/day 13541000 cu.m/year, with the recharge amount is about 300170 cu.m/day or 10956201 cu.m/year.